PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS PENYEBARAN KLINIK DAN PENGGUNA ALAT KONTRASEPSI DI BANDAR LAMPUNG - , S.Kom., M.Cs, Yulmaini (Jurnal Informatika, 2014)
Geographic information system, as computerized tool can be used to map and analyse existing object or occurance on earth surface. One of the implementations of geographic information system is clinics deployment and contraceptive users in Bandar Lampung. During this time, informations about clinics deployment information and contraceptive users in Bandar Lampung, is spread out by pamphlets from BKKBN, and so far, there is no particular application to help people to get information of clinics deployment by map. This research is meant to build a Geographic Information System about clinics deployment and contracetive users in Bandar Lampung. Data that required building geographic information system development are spatial data and non spatial data. Spatial data is data of Bandar Lampung map that contains of informations of districts in Bandar Lampung. While non-spatial data is administrative data that contains of informations of clinics deployment and contraceptive users in Bandar Lampung.Keywords: Geographic Information System, Contraceptions, Clinic Deployment.